Tulathromycin Exerts Proresolving Effects in Bovine Neutrophils by Inhibiting Phospholipases and Altering Leukotriene B(4), Prostaglandin E(2), and Lipoxin A(4) Production - Fischer, Carrie D. (American Society for Microbiology, 2014)
The accumulation of neutrophils and proinflammatory mediators, such as leukotriene B(4) (LTB(4)), is a classic marker of inflammatory disease. The clearance of apoptotic neutrophils, inhibition of proinflammatory signaling, and production of proresolving lipids (including lipoxins, such as lipoxin A(4) [LXA(4)]) are imperative for resolving inflammation. Tulathromycin (TUL), a macrolide used to treat bovine respiratory disease, confers immunomodulatory benefits via mechanisms that remain unclear. We recently reported the anti-inflammatory properties of TUL in bovine phagocytes in vitro and in Mannheimia haemolytica-challenged calves. The findings demonstrated that this system offers a powerful model for investigating novel mechanisms of pharmacological immunomodulation. In the present study, we examined the effects of TUL in a nonbacterial model of pulmonary inflammation in vivo and characterized its effects on lipid signaling. In bronchoalveolar lavage (BAL) fluid samples from calves challenged with zymosan particles (50 mg), treatment with TUL (2.5 mg/kg of body weight) significantly reduced pulmonary levels of LTB(4) and prostaglandin E(2) (PGE(2)). In calcium ionophore (A23187)-stimulated bovine neutrophils, TUL inhibited phospholipase D (PLD), cytosolic phospholipase A(2) (PLA(2)) activity, and the release of LTB(4). In contrast, TUL promoted the secretion of LXA(4) in resting and A23187-stimulated neutrophils, while levels of its precursor, 15(S)-hydroxyeicosatetraenoic acid [15(S)-HETE], were significantly lower. These findings indicate that TUL directly modulates lipid signaling by inhibiting the production of proinflammatory eicosanoids and promoting the production of proresolving lipoxins.